Ovariectomy in mice primes hippocampal microglia to exacerbate behavioral sickness responses - Kevin Sanchez; Sienna L. Wu; Reha Kakkar; Jeffrey S. Darling; Claire S. Harper; Laura K. Fonken (Brain, Behavior, & Immunity - Health, 2023)
Estrogens are a group of steroid hormones that promote the development and maintenance of the female reproductive system and secondary sex characteristics. Estrogens also modulate immune responses; estrogen loss at menopause increases the risk of inflammatory disorders. Elevated inflammatory responses in the brain can lead to affective behavioral changes, which are characteristic of menopause. Thus, here we examined whether loss of estrogens sensitizes microglia, the primary innate immune cell of the brain, leading to changes in affective behaviors. To test this question, adult C57BL/6 mice underwent an ovariectomy to remove endogenous estrogens and then received estradiol hormone replacement or vehicle. After a one-month recovery, mice received an immune challenge with lipopolysaccharide (LPS) or vehicle control treatment and underwent behavioral testing. Ovariectomized, saline-treated mice exhibited reduced social investigation compared to sham-operated mice. Furthermore, ovariectomized mice that received LPS exhibited an exacerbated decrease in sucrose preference, which was ameliorated by estradiol replacement. These results indicate that ovariectomy modulates affective behaviors at baseline and in response to an inflammatory challenge. Ovariectomy-related behavioral changes were associated with downregulation of Cx3cr1, a microglial receptor that limits activation, suggesting that estrogen loss can disinhibit microglia to immune stimuli. Indeed, estradiol treatment reduced ovariectomy-induced increases in Il1b and Il6 expression after an immune challenge. Changes in microglial reactivity following ovariectomy are likely subtle, as overt changes in microglial morphology (e.g., soma size and branching) were limited. Collectively, these results suggest that a lack of estrogens may allow microglia to confer exaggerated neuroimmune responses, thereby raising vulnerability to adverse affective- and sickness-related behavioral changes.